2011
DOI: 10.1093/toxsci/kfr298
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin Increases Oxidative Metabolism in HL-1 Cardiomyocytes as Shown by 13C Metabolic Flux Analysis

Abstract: Doxorubicin (DXR), an anticancer drug, is limited in its use due to severe cardiotoxic effects. These effects are partly caused by disturbed myocardial energy metabolism. We analyzed the effects of therapeutically relevant but nontoxic DXR concentrations for their effects on metabolic fluxes, cell respiration, and intracellular ATP. (13)C isotope labeling studies using [U-(13)C(6)]glucose, [1,2-(13)C(2)]glucose, and [U-(13)C(5)]glutamine were carried out on HL-1 cardiomyocytes exposed to 0.01 and 0.02 μM DXR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 56 publications
3
24
0
2
Order By: Relevance
“…We used HL-1 cells for in vitro study of MyBPC protein carbonylation. HL-1 cells have been used to study normal cardiomyocyte functions (34) and to study Dox-induced cytotoxicity and metabolic changes (35). Consistent with previous observations (35), less than 200 nM Dox was not toxic to cells within 24 h and significant MyBPC protein carbonylation and degradation were not observed under this concentration.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…We used HL-1 cells for in vitro study of MyBPC protein carbonylation. HL-1 cells have been used to study normal cardiomyocyte functions (34) and to study Dox-induced cytotoxicity and metabolic changes (35). Consistent with previous observations (35), less than 200 nM Dox was not toxic to cells within 24 h and significant MyBPC protein carbonylation and degradation were not observed under this concentration.…”
Section: Discussionsupporting
confidence: 62%
“…HL-1 cells have been used to study normal cardiomyocyte functions (34) and to study Dox-induced cytotoxicity and metabolic changes (35). Consistent with previous observations (35), less than 200 nM Dox was not toxic to cells within 24 h and significant MyBPC protein carbonylation and degradation were not observed under this concentration. We observed that 500 nM is the optimal concentration of Dox required to induce MyBPC carbonylation, degradation, and cytotoxicity in HL-1 cells at 24 h. Carbonylation and degradation of MyBPC were also observed in SHRs under cardiotoxic conditions (23).…”
Section: Discussionsupporting
confidence: 62%
“…In human podocytes, knockdown of SCO2 expression increased cleaved caspase-9 levels and release of cytochrome c, adding some support to the proposal by Mallipattu and colleagues that SCO2 may be a key KLF6 target for mediating protection against mitochondrial injury (22). The expression of a number of other mitochondrial genes was also reduced in podocyte-specific Klf6-knockout mice, including nuclear oxidation, and this may impose oxidative stress (25). This suggests that KLF6 contributes to progression of glomerular injury, at least in this model.…”
Section: Mitochondria and Podocyte Functionmentioning
confidence: 54%
“…Metabolic flux analysis has been applied for mammalian cells for a long time already but mostly only using metabolite balancing [8]. The labelling of extracellular excreted lactate and CO 2 has already been used in the past but only at metabolic steady state [8-11]. The use of other labelled metabolites, e.g.…”
Section: Introductionmentioning
confidence: 99%